2018
DOI: 10.1016/j.nmni.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Endocarditis in the Mediterranean Basin

Abstract: Infective endocarditis is a severe disease with high mortality. Despite a global trend towards an increase in staphylococcal aetiologies, in older patients and a decrease in viridans streptococci, we have observed in recent studies great epidemiologic disparities between countries. In order to evaluate these differences among Mediterranean countries, we performed a PubMed search of infective endocarditis case series for each country. Data were available for 13 of the 18 Mediterranean countries. Despite great d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…It is also the largest QFE series involving bovine jugular vein grafts such as Melody valves and Contegra conduits. Among the 502 patients with endocarditis, 234 (46.6%) had BCNE, which is consistent with the rates of BCNE in the Mediterranean basin (46-69%) (Gouriet et al, 2018). The rates of Q fever in all endocarditis and BCNE patients in our study were only 3.7% and 8.0%, respectively; however, this is probably an underestimation since many of the BCNE patients did not undergo serology.…”
Section: Discussionsupporting
confidence: 87%
“…It is also the largest QFE series involving bovine jugular vein grafts such as Melody valves and Contegra conduits. Among the 502 patients with endocarditis, 234 (46.6%) had BCNE, which is consistent with the rates of BCNE in the Mediterranean basin (46-69%) (Gouriet et al, 2018). The rates of Q fever in all endocarditis and BCNE patients in our study were only 3.7% and 8.0%, respectively; however, this is probably an underestimation since many of the BCNE patients did not undergo serology.…”
Section: Discussionsupporting
confidence: 87%
“…Since more than one-fourth of S. aureus strains were methicillin resistant and penicillin resistance was detected in more than one-fourth of S. viridans strains, the empirical use of vancomycin or daptomycin should be considered in accordance with the local susceptibility data. Although preliminary data stressed the importance of hospital-acquired pathogens [19], our data disclosed that as much as 18% of NVE cases were classified under hospitalacquired infection category. Furthermore, dental source, central catheters, and respiratory system appeared to be more significant sources in NVE while cardiac surgery was commonly associated to PVE.…”
Section: Discussionmentioning
confidence: 57%
“…In Italy, a regional Tuscany epidemiological study over 17 years showed an incidence rate of IE of 4.6/100,000 person-years, with a higher value in people older than 65 years (11.7/100,000 person-years) [5][6]. Recently, Gouriet et al (2018) reported a tremendous epidemiologic disparity among Mediterranean countries regarding etiology and diagnosis [7]. Blood culture is proof of continuous bacteremia and is one of the significant criteria for diagnosing IE [1][2][8][9].…”
Section: Introductionmentioning
confidence: 99%